Combination of Exercise Testing Criteria to Diagnose Lower Extremity Peripheral Artery Disease - Stivalet, Olivier; Paisant, Anita; Belabbas, Dihia; Le Faucheur, Alexis; Landreau, Philippe; Le Pabic, Estelle; Omarjee, Loukman; Mahé, Guillaume (Frontiers in Cardiovascular Medicine, 2021)
Objectives: Nothing is known about the interest of the combination of exercise tests to diagnose Lower-extremity Peripheral Artery Disease (LEPAD). The aim of this study was to assess if combining exercise testing criteria [post-exercise Ankle-Brachial Index (ABI) + exercise-oximetry (exercise-TcPO2)] improves the detection of lower limbs arterial stenoses as compared with post-exercise ABI using American Heart Association (AHA) criteria, or exercise-TcPO2 alone. Material and Methods: In a prospective monocentric study, consecutive patients with exertional-limb pain and normal resting-ABI referred to our vascular center (Rennes, France) were assessed from May 2016 to February 2018. All included patients had a computed tomography angiography (CTA), a resting-ABI, a post-exercise ABI and an exercise-TcPO2. AHA post-exercise criteria, new validated post-exercise criteria (post-exercise ABI decrease ≥18.5%, post-exercise ABI decrease <0.90), and Delta from Rest of Oxygen Pressure (Total-DROP) ≤-15mmHg (criterion for exercise-TcPO2) were used to diagnose arterial stenoses ≥50%. For the different combinations of exercise testing criteria, sensitivity or specificity or accuracies were compared with McNemar's test. Results: Fifty-six patients (mean age 62 ± 11 years old and 84% men) were included. The sensitivity of the combination of exercise testing criteria (post-exercise ABI decrease ≥18.5%, or post-exercise ABI decrease <0.90 or a Total-DROP ≤-15mmHg) was significantly higher (sensitivity = 81% [95% CI, 71–92]) than using only one exercise test (post-exercise AHA criteria (sensitivity = 57% [43–70]) or exercise-TcPO2 alone (sensitivity = 59% [45–72]). Conclusions: Combination of post-exercise ABI with Exercise-TcPO2 criteria shows better sensitivity to diagnose arterial stenoses compared with the AHA post-exercise criteria alone or Exercise-TcPO2 criteria used alone. A trend of a better accuracy of this combined strategy was observed but an external validation should be performed to confirm this diagnostic strategy.